G527(P) A review of the nutritional assessment of children with cerebral palsy. (May 2019) - Mitchell, G; Sidebotham, P
Abstract : Aims: To determine the most reliable method for a nutritional assessment in a child with cerebral palsy with a GMFCS level IV-V. Methods: The review is in four parts: A review of the reasons behind this vulnerable group being susceptible to malnutrition, looking at the causative factors affecting nutrition, and potential adverse effects. A literature review by searching Embase and Medline databases to review the evidence behind the most effective way to assess nutrition in children who are predominantly using a wheelchair. An audit reviewing children with cerebral palsy who were referred for gastrostomy placement, how their nutritional status was assessed and comparing against NICE standards for nutritional assessment in children and young people with cerebral palsy (https://www.nice.org.uk/guidance/ng62) A survey of 16 acute and community paediatricians as well as dieticians to review current practice, and establish opinion on what would be acceptable and feasible to do in clinic as well as explore potential barriers to implementing a change in practice. The information obtained from above was used to create a clinic proforma, along with a user guide, designed to standardise our assessments and bring them in line with current NICE guidance. Results: Literature review: 92 articles were identified through Embase and Medline. These were reviewed using Critical Appraisal Skills Programme (CASP) and the American National Institute for Health appraisal tool, and the most relevant evidence was summarised. Audit: 82 patient notes were reviewed electronically, 11 met audit criteria. 56% had their height and weight measured; 0% had further anthropometric measurements done if basic height and weight measurements were not performed. Survey: 21% feel their current practice gives an adequate reflection of nutritional status. 100% of respondents routinely measured weight; 79% height, 36% head circumference; 50% Body Mass Index. 21% request blood tests; 7% perform knee height if actual height is not possible; 43% look for physical signs of malnutrition. Concerns were highlighted over lack of appropriate equipment and training. Conclusions: There is wide variation in our practice and an evidence based approach to standardising practice is essential to ensure the most effective assessment. Potential barriers of lack of funding, education and training in anthropometry must be overcome.